W18O49 / graphene / phosphorylation / amidoximation electrode material and preparation and application thereof

By preparing W18O49/graphene/phosphorylated/geminoximetyl electrode materials, the problems of low uranium extraction efficiency in seawater and difficulty in regeneration of adsorbent materials in the prior art are solved, and efficient and stable recovery of uranyl ions is achieved.

CN119517637AActive Publication Date: 2025-02-25SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411670911.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The prior art has low efficiency in extracting uranium in seawater, the active sites of adsorbent materials are easily saturated and difficult to regenerate, which limits its application.

Method used

Using W18O49/graphene/phosphorylated/geminoximetyl electrode material, electrodes with high selectivity and stability were prepared by coating, carbonization, phosphorylation and geminoximetyl treatment of ammonium tungstate and graphene. Material.

Benefits of technology

It realizes efficient selective adsorption and recovery of uranyl ions, with a recovery efficiency of more than 95%, and has better cycle stability and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517637A_ABST
    Figure CN119517637A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode materials and nuclide recovery, and discloses a W18O49 / graphene / phosphorylation / amidoximation electrode material and preparation and application thereof. The preparation method comprises the following steps: dispersing ammonium tungstate and graphene in a trihydroxymethyl aminomethane solution, and heating and stirring for reaction to obtain a mixed solution; then adding dopamine hydrochloride, ethanol and ammonia water, stirring and reacting, and washing and drying a product to obtain a precursor; and carbonizing the obtained precursor in an inert atmosphere at the temperature of 600-900 DEG C to obtain a W18O49 / graphene material, then dispersing the W18O49 / graphene material in a hydroxylamine hydrochloride solution and / or a phytic acid solution for stirring reaction, and washing and drying the product to obtain the W18O49 / graphene / phosphorylation / amidoximation electrode material. The selective recovery efficiency of the obtained electrode material on uranyl ions can reach 95% or above, and the electrode material has wide application prospects in the field of nuclide uranium recovery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode materials and nuclide recovery, and specifically relates to a W 18 O 49 / Graphene / phosphorylation / amidoxime electrode materials and their preparation and applications. Background Art

[0002] With the rapid development of economy and the rapid growth of population, the use of non-renewable fossil energy such as coal and oil is increasing day by day, which has caused serious problems for society and environment, the greenhouse effect is becoming more and more serious, and energy shortage is becoming more and more obvious. As an indispensable nuclear fuel for the operation of nuclear power, the continuous supply of uranium is of great significance to the safe development of nuclear industry. In order to achieve the sustainable and green development of nuclear energy, the development of a stable, efficient, green and recyclable seawater uranium extraction technology is of great strategic significance to the development and application of uranium resources.

[0003] At present, domestic and foreign scholars have made certain progress in the technology of uranium extraction from seawater, but further efforts are needed to reach the industrial level. For decades, researchers have developed a variety of methods for uranium extraction from seawater, such as physical and chemical adsorption, solvent extraction, coprecipitation, biological treatment, ion exchange and membrane separation. However, the most widely used method for uranium extraction from seawater is physical and chemical adsorption. However, due to the limited surface area of ​​the adsorbent material, the uranium concentration in the ocean is low, the salinity is high and the environment is complex. At the same time, the active sites on the adsorbent material used to adsorb uranyl ions are quickly saturated, and the ideal uranium extraction effect cannot be achieved. Although these adsorbents have a certain adsorption capacity for uranyl ions, their removal capacity for low-concentration uranyl ions is limited, and the adsorbent is also prone to secondary migration and difficult to regenerate, which limits its application. Therefore, the development of an efficient and selective uranium extraction technology is of great significance to the sustainable development of nuclear energy.

[0004] Capacitive deionization technology is a new technology based on the theory of capacitive deionization, which has the characteristics of low energy consumption, low cost and environmental friendliness. Capacitive deionization technology has broad application prospects in domestic sewage treatment, tap water purification, industrial wastewater treatment and other aspects. Commonly used capacitive deionization forms: double-layer capacitors. A certain voltage is applied between the two electrodes. When the solution flows between the two electrodes, under the action of the electric field, the ions will move toward the electrode with opposite electrical properties and eventually be adsorbed on the electrode. Therefore, the concentration of the solution flowing out of the deionization device will decrease, achieving deionization. When the ions moving into the pores of the electrode material reach saturation, the two electrodes are reversely connected, and the ions in the pores are released again, so that the electrode can be regenerated. Commonly used carbon materials have large specific surface area, high conductivity, good electrochemical stability and rich pore structure. However, the existing carbon-based materials capture charged ions through the double-layer mechanism, and the extraction efficiency of uranyl ions is low. The introduction of pseudocapacitive materials can significantly improve the deionization capacity of capacitors. Unlike porous carbon electrodes that store ions in double-layer electrodes, pseudocapacitors can store ions through electrochemical effects such as ion intercalation and conversion. However, conversion reactions can easily cause large changes in the electrode volume, leading to severe electrode attenuation and poor stability. The use of ion intercalation reactions can avoid the above disadvantages. This is because the intercalation electrode has a larger interlayer spacing and can provide a larger ion storage space, thereby effectively improving the reversible capacity of the electrochemical reaction.

[0005] W 18 O 49 With high specific capacitance and adjustable interlayer spacing, it can provide a larger ion storage space for ion transport. At the same time, a larger interlayer spacing can also effectively increase the adsorption capacity of ions. 18 O 49 The material synthesis process is simple, there is no accumulation problem, it has good stability, and it is not easily soluble in acidic or alkaline solutions. 18 O 49 There is W in the lattice 4+ , W 5+ and W 6+ Multiple valence states result in too many electrons and lattice distortion between the interlayers. When the third phase cation is inserted, a large number of free electrons will gather on the lattice surface, which is conducive to the adsorption of cations. However, due to the single component W 18 O 49 Due to its low conductivity and small specific surface area, it is often limited in capacitive deionization. Summary of the invention

[0006] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a 18 O 49 / graphene / phosphorylation / amidoxime electrode material preparation method.

[0007] Another object of the present invention is to provide a W prepared by the above method. 18 O 49 / graphene / phosphorylation / amidoxime electrode materials.

[0008] Another object of the present invention is to provide the above-mentioned 18 O 49 / Application of graphene / phosphorylation / amidoxime electrode materials in the recovery of radionuclide uranium.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A W 18 O 49 / graphene / phosphorylation / amidoximation electrode material preparation method, comprising the following preparation steps:

[0011] (1) dispersing ammonium tungstate and graphene in a tris(hydroxymethyl)aminomethane solution and heating and stirring to react to obtain a mixed solution;

[0012] (2) dispersing dopamine hydrochloride, ethanol and ammonia water in the mixed solution of step (1) in sequence and stirring to react, and washing and drying the product to obtain a precursor;

[0013] (3) The precursor obtained in step (2) is carbonized in an inert atmosphere at a temperature of 600 to 900° C. to obtain W 18 O 49 / graphene materials;

[0014] (4) W obtained in step (3) 18 O 49 The graphene material is dispersed in a hydroxylamine hydrochloride solution and / or a phytic acid solution and stirred for reaction, and the product is washed and dried to obtain W 18 O 49 / graphene / phosphorylation / amidoxime electrode materials.

[0015] Furthermore, the mass concentration of the tris(hydroxymethyl)aminomethane solution in step (1) is 0.1-5 mg / mL.

[0016] Furthermore, the amount of ammonium tungstate added in step (1) is 0.1 to 4 times the mass of dopamine hydrochloride in step (2).

[0017] Furthermore, the amount of graphene added in step (1) is 0.1 to 1 times the mass of dopamine hydrochloride in step (2).

[0018] Furthermore, the heating and stirring reaction in step (1) refers to stirring the reaction at 30 to 80° C. for 0.1 to 6 hours.

[0019] Furthermore, the amount of ethanol added in step (2) is 0.1 to 200 times the mass of ammonium tungstate in step (1), and the addition of ethanol is beneficial to the dispersion of ammonium tungstate and graphene.

[0020] Furthermore, the amount of ammonia water added in step (2) is 0.1 to 5 times the mass of ammonium tungstate in step (1), and the addition of ammonia water is beneficial to the decomposition of ammonium tungstate.

[0021] Furthermore, the stirring reaction in step (2) refers to stirring the reaction at room temperature for 6 to 24 hours; the washing refers to washing with deionized water, and the drying refers to drying at a temperature of 100 to 140°C.

[0022] Furthermore, the inert atmosphere in step (3) refers to a nitrogen atmosphere or an argon atmosphere; and the carbonization treatment time is 5 to 500 minutes.

[0023] Furthermore, the mass concentration of the hydroxylamine hydrochloride solution in step (4) is 0.1-5 mg / mL; the mass concentration of the phytic acid solution is 0.1-200 mg / mL.

[0024] Furthermore, the stirring reaction in step (4) refers to stirring the reaction at room temperature for 6 to 24 hours; the washing refers to washing with deionized water; and the drying refers to drying at a temperature of 100 to 140°C.

[0025] A W 18 O 49 / graphene / phosphorylation / amidoxime electrode material is prepared by the above method.

[0026] Preferably, the W 18 O 49 The / graphene / phosphorylation / amidoxime electrode material is composed of nanospheres with a diameter of 10 to 50 nm, wherein the mass ratio of tungsten, oxygen, nitrogen, phosphorus and carbon is 1 to 20:1 to 30:1 to 40:0.1 to 10:1 to 100.

[0027] The above W 18 O 49 / Application of graphene / phosphorylation / amidoxime electrode materials in the recovery of radionuclide uranium.

[0028] Furthermore, the application method is: W 18 O 49 / graphene / phosphorylation / amidoxime electrode material is used as the negative electrode of the capacitive deionization device, and the activated carbon material is used as the positive electrode, and then the uranyl ions are recovered by capacitive adsorption.

[0029] Preferably, the voltage adsorbed by the capacitor is 0.1-5V.

[0030] The principle of the present invention is: by using ammonium tungstate and graphene to coat dopamine hydrochloride to obtain a precursor product, and further carbonizing the obtained precursor product under an inert atmosphere to obtain the required W 18 O 49 / graphene, the resulting W 18 O 49 / Graphene adsorbs hydroxylamine hydrochloride and / or phytic acid to obtain W 18 O 49 / graphene / phosphorylation / amidoxime electrode, the amino group contained in the amidoxime functional group and the N and O atoms in the oxime group can provide lone pairs of electrons to the uranium atom with an empty orbital, thereby forming a stable five-membered ring chelate. At the same time, according to the theory of soft and hard acids and bases, the amidoxime group belongs to a hard base ligand, which is more suitable for hard acid uranyl ions. In addition, while the amidoxime group is introduced, a phosphate group with auxiliary coordination ability can also be introduced. The phosphate group is a ternary medium-strong acid, the phosphate ion has a strong coordination ability, and the hydroxyl group (-OH) in the molecule forms a strong hydrogen bond with the oxygen atom in the uranyl ion, which is conducive to the capture of uranyl ions from water. The obtained electrode material is used for selective capacitance to recover uranyl ions, and the recovery efficiency of uranyl ions can reach more than 95%.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The preparation method of the present invention comprises adsorbing hydroxylamine hydrochloride and / or phytic acid to W 18 O 49 / graphene is phosphorylated and / or amidoximated to obtain W 18 O 49 / graphene / phosphorylation / amidoxime electrode material has binding sites with affinity for uranyl ions, which can significantly improve the selective adsorption effect of the electrode material on uranyl ions. 18 O 49 The selective recovery efficiency of uranyl ions of the / graphene / phosphorylation / amidoxime electrode materials at a voltage of 1.2V can reach more than 95%.

[0033] (2) Compared with conventional adsorption method, chemical precipitation method, ion exchange method and membrane separation method, the application method of the present invention in uranyl ion recovery has the advantages of high energy efficiency, environmental friendliness, low cost, etc., and has better cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 W prepared in Example 1 18 O 49 / Scanning electron microscope image of graphene / phosphorylation / amidoxime-treated electrode material.

[0035] Figure 2 W prepared in Example 118 O 49 / Transmission electron microscope image of graphene / phosphorylation / amidoxime-treated electrode material.

[0036] Figure 3 W prepared in Example 1 18 O 49 / Graphene / phosphorylation / amidoxime electrode material XPS and element content distribution diagram.

[0037] Figure 4 W prepared in Example 1 18 O 49 / graphene / phosphorylation / amidoximation electrode material, W prepared in Example 2 18 O 49 / graphene / phosphorylated electrode material and W prepared in Example 3 18 O 49 / Graphene / phosphorylation / amidoxime electrode materials for the recovery efficiency of uranyl ions.

[0038] Figure 5 W prepared in Example 1 18 O 49 / graphene / phosphorylation / amidoximation electrode material, W prepared in Example 2 18 O 49 / graphene / phosphorylated electrode material and W prepared in Example 3 18 O 49 / Graphene / phosphorylation / amidoxime electrode materials for the recovery efficiency of uranyl ions.

[0039] Figure 6 W prepared in Example 1 18 O 49 / Graphene / phosphorylation / amidoxime electrode material recovery efficiency of uranyl ions at different cycle numbers. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0041] Example 1

[0042] In this embodiment, a method based on W 18 O 49 / graphene / phosphorylation / amidoxime electrode material, the specific preparation steps are as follows:

[0043] (1) 1.2 g of ammonium tungstate powder and 0.1 g of graphene were weighed and dispersed in 200 mL of 1 mg / mL trishydroxyaminomethane solution, and reacted under magnetic stirring at 80° C. for 30 minutes to obtain a mixed solution.

[0044] (2) Weigh 0.4 g of dopamine hydrochloride and disperse it in the above mixed solution. Mix it under magnetic stirring at room temperature for 2 hours. Then add 160 mL of ethanol and stir it for 2 hours. Finally, add 1.2 mL of ammonia water and stir it for 2 hours. The product after the reaction is washed with deionized water, filtered, and dried at 120° C. to obtain precursor 1.

[0045] (3) The obtained precursor sample was placed in a tube furnace and subjected to heating carbonization treatment in an Ar inert atmosphere at a temperature of 750° C. for 180 minutes to obtain W 18 O 49 / Graphene.

[0046] (4) The obtained W 18 O 49 / graphene, dispersed in a mixed solution of 90mL deionized water and 10mL ethanol, then added with 0.1g hydroxylamine hydrochloride, magnetically stirred for reaction at room temperature for 30 minutes, added with 0.1mol / L sodium hydroxide to adjust the pH of the solution to 7, then magnetically stirred for reaction at 80°C for 6 hours, and the product after the reaction was washed with deionized water and filtered to obtain precursor 2.

[0047] (5) The obtained precursor 2 was dispersed in a 10% by mass phytic acid aqueous solution, and reacted under magnetic stirring at room temperature for 10 hours. The product after the reaction was washed with deionized water, filtered, and dried at 120° C. to obtain W 18 O 49 / graphene / phosphorylation / amidoxime electrode materials.

[0048] This embodiment W 18 O 49 The scanning electron microscopy and transmission electron microscopy images of the electrode materials are shown in Figure 2. Figure 1 and Figure 2 As shown, W 18 O 49 The element distribution diagram of graphene / phosphorylation / amidoxime electrode materials is shown in Figure 2. Figure 3 As shown. It can be seen that the W obtained by the present invention 18 O 49 The / graphene / phosphorylation / amidoxime electrode material is composed of nanospheres with a diameter of 10 to 50 nm, wherein the mass ratio of tungsten, oxygen, nitrogen, phosphorus and carbon is 2.16:12.09:1.56:0.37:83.82.

[0049] The W obtained in this embodiment 18 O 49 / Application of graphene / phosphorylation / amidoxime electrode materials in uranyl ion recovery. The specific application methods are as follows:

[0050] The obtained W 18 O 49 / graphene / phosphorylation / amidoxime electrode material is used as the negative electrode of the capacitive deionization device, and activated carbon is used as the positive electrode of the capacitive deionization device. Under the action of 1.2V voltage, the capacitive adsorption of uranyl ions in uranyl nitrate solutions of different concentrations (10ppm, 30ppm, 50ppm, 70ppm, 90ppm) is carried out. The solution adsorbed by the capacitive adsorption is tested by ICP-OES, and the uranyl ion recovery rate is calculated. The test results are as follows: Figure 4 As shown. Figure 4 As a result, it can be seen that the W 18 O 49 The recovery efficiency of the / graphene / phosphorylation / amidoxime electrode material for uranyl ions with a concentration of 10ppm is 99.98%, the recovery efficiency of uranyl ions with a concentration of 30ppm is 99.97%, the recovery efficiency of uranyl ions with a concentration of 50ppm is 99.96%, the recovery efficiency of uranyl ions with a concentration of 70ppm is 99.95%, and the recovery efficiency of uranyl ions with a concentration of 90ppm is 99.94%.

[0051] The obtained W 18 O 49 / graphene / phosphorylation / amidoxime electrode material is used as the negative electrode of the capacitor deionization device, and activated carbon is used as the positive electrode of the capacitor deionization device. Under the action of 1.2V voltage, the capacitor adsorbs uranyl ions in a mixed solution of 10ppm uranyl nitrate and 100ppm sodium chloride. The solution adsorbed by the capacitor is tested by ICP-OES to calculate the recovery rate of uranyl ions. The test results are as follows: Figure 5 As shown. Figure 5 As a result, it can be seen that the W 18 O 49 The recovery efficiency of uranyl ions of the / graphene / phosphorylation / amidoxime electrode material is 99.97%.

[0052] At the same time, the obtained W 18 O 49 / graphene / phosphorylation / amidoxime electrode material is used as the negative electrode of the capacitor deionization device, and activated carbon is used as the positive electrode of the capacitor deionization device. Under the action of 1.2V voltage, the capacitor adsorbs uranyl ions in a mixed solution of 10ppm uranyl nitrate and 100ppm sodium chloride. The solution adsorbed by the capacitor at different cycle times was tested by ICP-OES to calculate the uranyl ion recovery rate. The test results are shown in Figure 6 As shown. Figure 6 As a result, it can be seen that the W 18 O 49 / graphene / phosphorylation / amidoxime electrode materials have high and stable recovery efficiency for uranyl ions.

[0053] Example 2

[0054] In this embodiment, a method based on W 18 O 49 / graphene / amidoxime material, compared with Example 1, the preparation process did not adsorb phytic acid molecules, and the specific preparation steps were as follows:

[0055] Steps (1) to (3) are the same as those in Example 1.

[0056] (4) The obtained W 18 O 49 / graphene, dispersed in a mixed solution of 90mL deionized water and 10mL ethanol, then added 0.1g hydroxylamine hydrochloride, stirred magnetically for 30 minutes at room temperature, added 0.1mol / L sodium hydroxide to adjust the pH of the solution to 7, then stirred magnetically for 6 hours at 80°C, the product after the reaction was washed with deionized water, filtered, and dried at 120°C to obtain W 18 O 49 / graphene / amidoxime electrode materials.

[0057] The W obtained in this embodiment 18 O 49 The application of the graphene / amidoxime material in the recovery of uranyl ions is the same as in Example 1. The solution adsorbed by the capacitor is tested by ICP-OES to calculate the recovery rate of uranyl ions. The test results are as follows: Figure 4 As shown. Figure 4 As a result, it can be seen that the W 18 O 49 The recovery efficiency of the / graphene / amidoxime electrode material for uranyl ions at a concentration of 10ppm is 95.96%, the recovery efficiency of uranyl ions at a concentration of 30ppm is 95.9%, the recovery efficiency of uranyl ions at a concentration of 50ppm is 95.85%, the recovery efficiency of uranyl ions at a concentration of 70ppm is 95.80%, and the recovery efficiency of uranyl ions at a concentration of 90ppm is 95.77%. Under the action of a voltage of 1.2V, the uranyl ions in a mixed solution of 10ppm uranyl nitrate and 100ppm sodium chloride are capacitively adsorbed. The capacitively adsorbed solution is tested by ICP-OES to calculate the uranyl ion recovery rate. The test results are as follows: Figure 5 As shown. Figure 5 As a result, it can be seen that the W 18 O 49 The recovery efficiency of uranyl ions of the / graphene / amidoxime electrode material is 95.96%.

[0058] By comparing the results with those of Example 1, it can be seen that the recovery rate of the electrode material for uranyl ions can be further improved by introducing phosphorus-containing active sites by adsorbing phytic acid molecules.

[0059] Example 3

[0060] In this embodiment, a method based on W 18 O 49 / graphene / phosphorylated material, compared with Example 1, hydroxylamine hydrochloride is not added in the preparation process, and the specific preparation steps are as follows:

[0061] Steps (1) to (3) are the same as those in Example 1.

[0062] (4) The obtained W 18 O 49 / graphene was dispersed in a 10% phytic acid aqueous solution and reacted under magnetic stirring at room temperature for 10 hours. The product after the reaction was washed with deionized water, filtered, and dried at 120°C to obtain W 18 O 49 / graphene / phosphorylated electrode materials.

[0063] The W obtained in this embodiment 18 O 49 / Graphene / Phosphorylation is applied in the recovery of uranyl ions. The specific application method is the same as in Example 1. The solution adsorbed by capacitance is tested by ICP-OES to calculate the recovery rate of uranyl ions. The test results are as follows: Figure 4 As shown. Figure 4 As a result, it can be seen that the W 18 O 49 The recovery efficiency of the / graphene / phosphorylated electrode material for uranyl ions at a concentration of 10ppm is 96.98%, the recovery efficiency of uranyl ions at a concentration of 30ppm is 96.89%, the recovery efficiency of uranyl ions at a concentration of 50ppm is 96.78%, the recovery efficiency of uranyl ions at a concentration of 70ppm is 96.66%, and the recovery efficiency of uranyl ions at a concentration of 90ppm is 96.6%. Under the action of a voltage of 1.2V, the uranyl ions in a mixed solution of 10ppm uranyl nitrate and 100ppm sodium chloride are capacitively adsorbed. The solution adsorbed by the capacitive is tested by ICP-OES to calculate the recovery rate of uranyl ions. The test results are as follows: Figure 5 As shown. Figure 5 As a result, it can be seen that the W 18 O 49 The recovery efficiency of uranyl ions of the / graphene / phosphorylated electrode material is 96.97%.

[0064] By comparing the results with those of Example 1, it can be seen that the recovery rate of the electrode material for uranyl ions can be further improved by adding hydroxylamine hydrochloride to introduce amidoxime groups.

[0065] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A W 18 O 49 / graphene / phosphorylation / amidoximation electrode material preparation method, characterized in that, The method comprises the following preparation steps: (1) dispersing ammonium tungstate and graphene in a tris(hydroxymethyl)aminomethane solution and heating and stirring to react to obtain a mixed solution; (2) dispersing dopamine hydrochloride, ethanol and ammonia water in the mixed solution of step (1) in sequence and stirring to react, and washing and drying the product to obtain a precursor; (3) The precursor obtained in step (2) is carbonized in an inert atmosphere at a temperature of 600 to 900° C. to obtain W 18 O 49 / graphene materials; (4) W obtained in step (3) 18 O 49 The graphene material is dispersed in a hydroxylamine hydrochloride solution and / or a phytic acid solution and stirred for reaction, and the product is washed and dried to obtain W 18 O 49 / graphene / phosphorylation / amidoxime electrode materials.

2. A W according to claim 1 18 O 49 / graphene / phosphorylation / amidoximation electrode material preparation method, characterized in that, The mass concentration of the tris(hydroxymethyl)aminomethane solution in step (1) is 0.1 to 5 mg / mL; the amount of ammonium tungstate added is 0.1 to 4 times the mass of dopamine hydrochloride in step (2); the amount of graphene added is 0.1 to 1 times the mass of dopamine hydrochloride in step (2); and the heated stirring reaction refers to stirring the reaction at 30 to 80° C. for 0.1 to 6 hours.

3. A W according to claim 1 18 O 49 / graphene / phosphorylation / amidoximation electrode material preparation method, characterized in that, The amount of ethanol added in step (2) is 0.1 to 200 times the mass of ammonium tungstate in step (1); the amount of ammonia water added is 0.1 to 5 times the mass of ammonium tungstate in step (1); the stirring reaction refers to stirring the reaction at room temperature for 6 to 24 hours; the washing refers to washing with deionized water, and the drying refers to drying at a temperature of 100 to 140°C.

4. A W according to claim 1 18 O 49 / graphene / phosphorylation / amidoximation electrode material preparation method, characterized in that, The inert atmosphere in step (3) refers to a nitrogen atmosphere or an argon atmosphere; the carbonization treatment time is 5 to 500 minutes.

5. A W according to claim 1 18 O 49 / graphene / phosphorylation / amidoximation electrode material preparation method, characterized in that, The mass concentration of the hydroxylamine hydrochloride solution in step (4) is 0.1 to 5 mg / mL; the mass concentration of the phytic acid solution is 0.1 to 200 mg / mL; the stirring reaction refers to stirring the reaction at room temperature for 6 to 24 hours; the washing refers to washing with deionized water; and the drying refers to drying at a temperature of 100 to 140°C.

6. A W 18 O 49 / graphene / phosphorylation / amidoximation electrode material, characterized in that: It is prepared by the method according to any one of claims 1 to 5.

7. A W according to claim 6 18 O 49 / graphene / phosphorylation / amidoximation electrode material, characterized in that: The W 18 O 49 The / graphene / phosphorylation / amidoxime electrode material is composed of nanospheres with a diameter of 10 to 50 nm, wherein the mass ratio of tungsten, oxygen, nitrogen, phosphorus and carbon is 1 to 20:1 to 30:1 to 40:0.1 to 10:1 to 100.

8. A W according to claim 6 or 7 18 O 49 / Application of graphene / phosphorylation / amidoxime electrode materials in the recovery of radionuclide uranium.

9. The use according to claim 8, characterized in that: The application method is: W 18 O 49 / graphene / phosphorylation / amidoxime electrode material is used as the negative electrode of the capacitive deionization device, and the activated carbon material is used as the positive electrode, and then the uranyl ions are recovered by capacitive adsorption.

10. The use according to claim 9, characterized in that: The voltage adsorbed by the capacitor is 0.1-5V.

Citation Information

Patent Citations

  • Polyamidoxime modified fluorinated graphene modified electrode as well as preparation method and application thereof

    CN117451805A

  • Carbon-based adsorbent with high-efficiency adsorption performance on uranium as well as preparation method and application of carbon-based adsorbent

    CN117696009A

  • Preparation method of nitrogen / phosphorus-containing polyfunctional group axially modified fiber and application of nitrogen / phosphorus-containing polyfunctional group axially modified fiber in extraction of uranium from seawater

    CN118002098A

Cited By

  • Advanced uranium treatment and resource collaborative recovery method for associated mineral radioactive wastewater

    CN122102319A

  • Associated mine radioactive wastewater uranium deep treatment and resource collaborative recovery method

    CN122102319B